Respostas

A melhor resposta!
  • Usuário do Brainly
2014-06-19T23:08:18-03:00
A) x² - 4x - 5 = 0

x² - 4x - 5 = 0
Δ = b² - 4 . a . c
Δ = (- 4)² - 4 . 1 . (- 5)
Δ = 16 + 20
Δ = 36

x = (- b ± √Δ)/(2 . a)
x = (- (- 4) ± √36)/(2 . 1)
x = (4 ± 6)/2

x' = (4 + 6)/2
x' = 10/2
x' = 5

x'' = (4 - 6)/2
x'' = - 2/2
x'' = - 1

S = {- 1, 5}

B) x² + 2x - 8 = 0

x² + 2x - 8 = 0
Δ = b² - 4 . a . c
Δ = 2² - 4 . 1 . (- 8)
Δ = 4 + 32
Δ = 36

x = (- b 
± √Δ)/(2 . a)
x = (- 2 ± √36)/(2 . 1)
x = (- 2 ± 6)/2

x' = (- 2 + 6)/2
x' = 4/2
x' = 2

x'' = (- 2 - 6)/2
x'' = - 8/2
x'' = - 4

S = {- 4, 2}

C) - x² + 10x - 24 = 0

- x² + 10x - 24 = 0
Δ = b² - 4 . a . c
Δ = 10² - 4 . (- 1) . (- 24)
Δ = 100 - 96
Δ = 4

x = (- b ± √Δ)/(2 . a)
x = (- 10 ± √4)/(2 . (- 1))
x = (- 10 ± 2)/- 2

x' = (- 10 + 2)/- 2
x' = - 8/- 2
x' = 8/2
x' = 4

x'' = (- 10 - 2)/- 2
x'' = - 12/- 2
x'' = 12/2
x'' = 6

S = {4, 6}

D) - x² - 2x + 3 = 0

- x² - 2x + 3 = 0
Δ = b² - 4 . a . c
Δ = (- 2)² - 4 . (- 1) . 3
Δ = 4 + 12
Δ = 16

x = (- b ± √Δ)/(2 . a)
x = (- (- 2) ± √16)/(2 . (- 1))
x = (2 ± 4)/- 2

x' = (2 + 4)/- 2
x' = 6/- 2
x' = - 6/2
x' = - 3

x'' = (2 - 4)/- 2
x'' = - 2/- 2
x'' = 2/2
x'' = 1

S = {- 3, 1}
2 5 2
2014-06-20T13:08:22-03:00
A) x²-4x-5=0
b) x²+2x-8=0
c) -x²+10x-8=0    ou x²-10x+8=0
d -x²-2x+3=0       ou x²+2x-3=0
equação do 2º grau ax²+bx+c
Δ=b²-4ac
x=-b +-√Δ    para x' + para x" -
       2a
substitua a, b e c nas fórmulas e terás os resultados abaixo
a) Δ=36        x'= 5 x"=-1
b) Δ=36        x'=2  x"=-4
c) Δ=68        x'= 9 8/65  x"=57/65
d) Δ=16        x'= 1    x"=-3